2021
DOI: 10.1111/hsc.13404
|View full text |Cite
|
Sign up to set email alerts
|

Family caregivers' and professionals' experiences of supporting people living with dementia’s nutrition and hydration needs towards the end of life

Abstract: The aim of this paper was to understand the needs of family caregivers and professionals supporting people living with dementia with eating and drinking difficulties towards the end of life and the strategies they use to overcome them. A total of 41 semi‐structured interviews with family caregivers (n = 21) and professionals (n = 20) were conducted in London and surrounding areas of England. Interviews were audio‐recorded and transcribed verbatim. Four themes were identified: caregivers accessing and seeking h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“… 31 This may involve the use of risk feeding and decisions to withhold or withdraw burdensome interventions, including ANH. Some families may find this difficult due to cultural beliefs or emotional unpreparedness, 32 , 33 which can be overlooked during discussions 34 , 35 and lead to conflict between family carers and staff.…”
Section: Discussionmentioning
confidence: 99%
“… 31 This may involve the use of risk feeding and decisions to withhold or withdraw burdensome interventions, including ANH. Some families may find this difficult due to cultural beliefs or emotional unpreparedness, 32 , 33 which can be overlooked during discussions 34 , 35 and lead to conflict between family carers and staff.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cooperation among those living with the patients is essential for food support. The study by Barrado-Martín et al in 2022 [ 19 ] indicated the importance of professionals providing education and support to family caregivers for the nutrition of people with dementia. Therefore, the role of visiting staff, including visiting managerial dieticians, dental hygienists, and dentists, may be crucial in educating people about food support.…”
Section: Discussionmentioning
confidence: 99%
“…Family carers should be provided with clear goals of care and a palliative care plan to support eating and drinking at the end-of-life, for example, risk feeding, mouth care and positioning [ 36 ]. Expression of a commitment to continuing care and regular communication could also restore the hope of those involved and prevent guilty feelings towards the death of the person with dementia [ 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%